An estimation of the Banach-Mazur distance between the space of convergent sequences and a concrete model of a space of affine continuous functions - Villada Bedoya, Jeimer (Topological Methods in Nonlinear Analysis, 2025)
In this paper c denotes the space of convergent sequences endowed with the supremum norm and W is the hyperplane of c defined by W={ (x(i))c: _i→∞(x(1)+x(2))/2}. We pose the problem of determining the Banach-Mazur distance d(c,W) and present a method to estimate such distance from below together with tight bounds for d(W,c).